Espsñol Inclusive leadership strategies to strengthen the inclusive practice of teachers in the city of Guayaquil - Ecuador - Barre-Bustamante, Jenny (2022)
This article is oriented to the analysis of inclusive leadership strategies used by teachers in their daily work. The study was conducted in the educational units Río Marañón and Unidad educativa Juan Diego Cuauhtlatoatzin in the city of Guayaquil-Ecuador. Among the objectives of this research are to determine which inclusive leadership competencies are applied in the classroom and to identify the characteristics of a correct dynamic management of teaching and learning processes in diversity. The methodology is projective-propositional with a quantitative approach; the design is non-experimental. The results show that the majority of teachers, within their functions, have some shortcomings in incorporating factors of inclusiveness in their curriculum, for example, the use of support resources to prevent barriers to student learning. In addition to this, there are also failures in management leadership, as it is not in line with the needs of inclusive learning. A correct diversification of the objectives of respect for diversity and the development of inclusive competencies with the improvement of the professional profile of teachers is therefore recommended, with the use of a guide of inclusive leadership guidelines that contains guidelines for the monitoring of teaching practice.